A new species of the genus Xya Latreille, 1809 (Orthoptera, Tridactyloidea, Tridactylidae) from Sichuan, China - Cao, Cheng-Quan; Shi, Jian-Ping; Hu, Yu-Lin (Zootaxa, 2017)
A new species Xya leshanensis sp. nov. of the genus Xya Latreille, 1809 from Sichuan, China is described in this paper. It is similar to Xya nitobei (Shiraki, 1913), but differs from latter by apical part of antennae joint almost as same as basal part in width; width of pronotum 1.25 times its length; hind wing long, extending over the end of abdomen distinctly; hind femur with four small yellowish-white spots on upper side; epiproct with a pair of large spines laterally directed on posterior angle, apical half narrow distinctly. Type specimens are deposited in the College of Life Science, Leshan Normal University, Leshan 614004, China.